PERAMALAN PENJUALAN BERAS DI TOKO BAROKAH RICE CILEUNGSI MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Galih Ahmad Zaidan; Muhammad Ibnu Dwi Rizaldy, Paduloh (Jurnal Ekonomi dan Bisnis, 2024)
Barokah Rice Store is one of the famous rice stores in Cileungsi, West Java. This store has many customers and the demand for rice continues to increase. The issue Barokah Rice Store is facing is the imbalance between the market's supply and demand for rice. Forecasting is necessary for eflective and successful planning. Because of this, forecasting techniques are essential for making future event predictions. Sales data on rice was obtained from Barokah Rice Store for the 2020– 2024 period. This method basically uses past data that has been exponentially weighted against earlier or newer observation values to smooth it. Brown developed Brown's double exponential smoothing, a linear model. This double exponential smoothing method is used when the data shows a trend. As per the findings of this investigation, the most precise α parameter for forecasting the number of rice sales at Toko Barokah Rice. Additionally, every month since 2022, the Barokah Rice Store's projected results for rice sales have declined